Insight into potential mechanisms of hypobaric hypoxia–induced learning and memory deficit – Lessons from rat studies - Qaid, EYA; Zakaria, R; Sulaiman, SF; Yusof, NA Mohd; Shafin, Nazlahshaniza; Othman, Zahiruddin; Ahmad, AH; Aziz, CB Abd (SAGE Publications, 2017)
Impairment of memory is one of the most frequently reported symptoms during sudden hypoxia exposure in human. Cortical atrophy has been linked to the impaired memory function and is suggested to occur with chronic high-altitude exposure. However, the precise molecular mechanism(s) of hypoxia-induced memory impairment remains an enigma. In this work, we review hypoxia-induced learning and memory deficit in human and rat studies. Based on data from rat studies using different protocols of continuous hypoxia, we try to elicit potential mechanisms of hypobaric hypoxia–induced memory deficit.